Optimalisasi Distribusi Dana APBN Ke Daerah Otonom - Aldo Yanuarto; Muhammad Syahbintang Maesa Putra; Novita Angraeni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Optimizing the distribution of State Revenue and Expenditure Budget (APBN) funds to autonomous regions is a strategic step to accelerate equitable development, improve public services, and encourage regional independence. Fund transfers such as the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH) play a central role in supporting infrastructure development and developing local potential. However, the implementation of fund distribution faces challenges such as imbalances in allocation between regions, low planning accuracy, and weak synergy between central and regional governments. This research uses normative legal methods to analyze regulations and fund management strategies, with case studies of regions that have successfully utilized APBN funds. The study highlights the critical role of efficiency, transparency, and effective supervision.